A Review Into Management As A Dynamic Function & The Development And Response To Changes In Economic, Socio-Political, Or Technological Conditions - Susu, Wu; Bhaumik, Amiya (Journal of Neonatal Surgery, 2025)
One such approach is to dynamically manage the workplace in such a manner that knowledge exchange is encouraged. Managers that adopt a dynamic approach shape their workplaces in the here and now. There is a lot of flexibility in the working structure, with jobs organized into loose clusters with their own schedules. Tasks should be grouped together, and group members should be physically close to each other so that data relevant to the intra-group task is readily available. Additionally, activities should be organized and timed such that information can be easily shared. A multitude of factors reflect the ever-changing nature of the environment. These include modifications to the make-up and organization of task sets and groups, the sequence in which these groups manifest, the duration and nature of tasks, and the standards for naming data pertinent to these tasks. The next step in reaching this objective is to formulate the issue mathematically. Researchers devised a clustering approach to address issues. The procedure is explained in detail with the help of several examples. Plus, points include the fact that the proposed approach may be useful in the dynamic management of different types of resources needed to complete the tasks.